Coordinating bioorthogonal reactions with two tumor-microenvironment-responsive nanovehicles for spatiotemporally controlled prodrug activation. Issue 8 (22nd January 2020) - Zuo, Liping; Ding, Jingjing; Li, Changkun; Lin, Feng; Chen, Peng R.; Wang, Peilin; Lu, Guihong; Zhang, Jinfeng; Huang, Li-Li; Xie, Hai-Yan
Abstract : Spatiotemporally controlled activation: Dox-TCO loaded low pH-sensitive nanovehicles and Tz-containing MMP-2-sensitive nanocarriers simultaneously dissociated in tumor microenvironment, with Dox locally liberated through IEDDA biorthogonal reaction. Abstract : Precise activation of prodrugs in tumor tissues is critical to ensuring specific antitumor efficacy, meanwhile reducing the serious adverse effects. Here, a spatiotemporally controlled prodrug activation strategy was provided by integrating the inverse electron demand Diels–Alder (IEDDA) reaction with two tumor-microenvironment-responsive nanovehicles. The prodrug (Dox-TCO) and [4-(6-methyl-1, 2, 4, 5-tetrazin-3-yl)phenyl]methanamine (Tz) were separately camouflaged into low pH and matrix metalloproteinase 2 (MMP-2) sensitive micellar nanoparticles. After systemic administration, only in the tumor tissues could both the nanovehicles dissociate via responding to two special tumor microenvironments, with Dox-TCO and Tz released and then immediately triggering the prodrug activation through the IEDDA reaction. The hierarchically regulated and locally confined Dox liberation led to dramatically decreased side-effects that were much lower than those of the clinical Doxorubicin Hydrochloride Liposomal Injection (Doxil), while the antitumor therapeutic effect was potent.